In‐Class vs. Online Testing in University‐Level Language Courses: A Research Report. (3rd December 2015) - VanPatten, Bill; Trego, Daniel; Hopkins, Walter P.
Abstract: Against the background of concerns for how paper‐and‐pencil testing fits into contemporary language teaching, this brief research report presents the findings of a first study on the difference in scores between in‐class testing and online testing in a communicative and proficiency‐oriented program. A total of 244 students of third‐semester Spanish at the university level participated. One hundred twenty‐four took tests online, while 120 took tests in class. Results showed no difference between the scores, suggesting that at least for this particular kind of program, in‐class testing can be altered and moved online, freeing up class time for alternative measurements (in this case, curriculum‐specific can‐do statements).